Comparative Characteristics of QT Interval Measurements on ECG Performed Manually and by Automated Method in Male Patients at Rest - Vadim A. Dulskiy (Journal of Global Pharma Technology, 2020)
In the medical practice of cardiologists, cases of incorrect measurement and interpretation of QT interval length are very frequent. The consequences make an incorrect diagnosis and inadequate treatment. The aim of this work is to investigate the efficiency of measuring the QT interval length on an ECG in manual mode and automated mode at rest among male patients. The sample included 3925 ECGs performed among males aged over 15 years old. Each measurement of QT, QTc intervals was performed both in manual and automatic modes. The numerical values matched only in 4.3% of cases. Automatic interval measurements exceeded the real values in 83.8% of cases. The prolongation of QTc intervals over 440 ms in the automatic mode was detected in 20.4% of cases. Over diagnosis was noted in 17.4% of cases. As a conclusion, manual adjustment is required in most cases measurements of prolonged QT, QTc intervals measured in automatic mode. Among the prevailing errors in automatic measurement, the most common were connected with T-waves (lack of diagnosis of T-wave displacement, its low amplitude and alternation). These erroneous measurements amounted to 53.3% of all measurements in automatic mode. The uncertain wave Q (R) accounted for 35.0% of all cases. In addition, 8.3% of cases were attributed to an undetected diagnosis of differences between manual and automatic methods. Keywords: T wave, Manual ECG diagnostics, Automatic ECG diagnostics, interval lengths QT, QTc.